D'Aulaires' Book of Norse myths - D'Aulaire, Ingri, 1904-1980 (New York Review of Books, 2005)
A collection of Norse myths describing the exploits of the Aesir gods and goddesses, beginning with the creation of the world and ending with the day of reckoning. The D'Aulaires provide an introduction to Norse legends, telling stories of Odin the all father, Thor the thunder god and the theft of his hammer, Loki the mischievous god of the Jotun Race, and Ragnarokk, the destiny of the gods. Meet Bragi, the god of poetry, and the famous Valkyrie maidens protecting Odin's Valhalla, among other gods, goddesses, heroes, and giants.